Development of Standard Test Specimens for Competency Improvement of Non-destructive Test (NDT) Personnel—Industrial Radiography - Sutanto, Jepri; Iswanto, Iswanto; Sumirat, Iwan; Pramutadi Andi Mustari, Asril; Permana, Sidik (Universitas Muhammadiyah Yogyakarta, 2025)
Test specimens made of low-carbon SS400 steel in the form of plates and pipes will be manufactured for use by certification and training institutions. Currently, test specimens in Indonesia are imported, resulting in higher operational costs. Therefore, the domestic fabrication of test specimens is conducted to address this issue and improve the competency of NDT personnel. Radiographic techniques are applied to evaluate defects and verify acceptance criteria. Plate specimens with a geometry of 350 mm x 200 mm and pipes with a diameter of 2